Endoscopic treatment with lumen-apposing metal stent in a patient with esophageal stricture and esophagobronchial fistula: a case report - Zhang, Mengmeng; Tang, Hao; Feng, Yunlu; Yang, Aiming (Frontiers in Medicine, 2025)
Endoscopic interventions for postoperative esophageal strictures and fistulas are inherently challenging. The use of conventional self-expandable metallic stents has been restricted due to high migration rates. There has been no report about malignant esophageal stricture and postoperative fistula managed with a lumen-apposing metal stent (LAMS). We present a case of refractory postoperative anastomotic stricture and esophagobronchial fistula following esophagectomy. Endoscopic deployment of a LAMS effectively relieved the obstruction and sealed the fistula, with the patient tolerating the procedure well and experiencing sustained symptom resolution for 4 weeks. This case suggests the potential role of LAMS in maintaining luminal patency and sealing fistulas. Endoscopic ultrasound-guided LAMS placement should be a technically feasible, effective and minimally invasive approach for postoperative esophageal stenosis and fistula.